Efektivitas Virtual Reality terhadap Penurunan Nyeri Prosedural pada Anak dengan Kanker - Apriyani, Apriyani; Afiyanti, Yati; Nuraini, Tuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of Virtual Reality (VR) to reduce procedural pain in children with cancer. The method use is a systematic review by collecting articles from the Proquest, Sage Journals, ScienceDirect and PubMed databases. The results describe that children with cancer in the VR group reported lower pain scores compared to the control group, both pain scores reported by children and pain scores reported by parents. Conclusions, the use of VR is effective in reducing prosedural pain in children with cancer. Keywords: Children With Cancer, Procedural Pain, Virtual Reality